2020
DOI: 10.1183/13993003.02130-2020
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and clinical impact of out-of-ICU noninvasive respiratory support in patients with COVID-19-related pneumonia

Abstract: IntroductionThe Coronavirus 2(SARS-CoV-2) outbreak spread rapidly in Italy and the lack of intensive care unit(ICU) beds soon became evident, forcing the application of noninvasive respiratory support(NRS) outside the ICU, raising concerns over staff contamination. We aimed to analyse the safety of the hospital staff, the feasibility, and outcomes of NRS applied to patients outside the ICU.MethodsIn this observational study, data from 670 consecutive patients with confirmed COVID-19 referred to the Pulmonology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
295
5
18

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 243 publications
(361 citation statements)
references
References 21 publications
17
295
5
18
Order By: Relevance
“…In our study cohort, the intubation rate was 45%, also taking into account those patients (n = 30) excluded from the study because intubated on the same day CPAP was started. This intubation rate is similar to that observed in non-COVID-19 ARF patients treated with NPPV, 26 but almost twice as high as that reported by two large studies on CPAP-treated COVID-19 patients (25% 4 and 22% 5 ), comprising both “do-not-intubate” and “candidate for intubation” patients. In the cohort of patients included in the study by Franco et al, 4 the severity of hypoxemic ARF, as assessed by PaO 2 /FiO 2 is lower than in our investigation, which might explain the lower rate of CPAP failure.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In our study cohort, the intubation rate was 45%, also taking into account those patients (n = 30) excluded from the study because intubated on the same day CPAP was started. This intubation rate is similar to that observed in non-COVID-19 ARF patients treated with NPPV, 26 but almost twice as high as that reported by two large studies on CPAP-treated COVID-19 patients (25% 4 and 22% 5 ), comprising both “do-not-intubate” and “candidate for intubation” patients. In the cohort of patients included in the study by Franco et al, 4 the severity of hypoxemic ARF, as assessed by PaO 2 /FiO 2 is lower than in our investigation, which might explain the lower rate of CPAP failure.…”
Section: Discussionsupporting
confidence: 86%
“…More recently, a multicentre observational study has shown that CPAP along with HFNC and NPPV can be readily applied outside of the ICU environment during COVID-19. 4 However, intubation after CPAP failure has been shown to occur in 22–25% 5 of patients, and other studies on noninvasive ventilation have reported that delayed intubation might worsen patient survival. 6 For this reason, the use of CPAP in COVID-19 patients is still under debate.…”
Section: Introductionmentioning
confidence: 99%
“…However, data is scarce regarding the impact of IMCU on mortality of severe COVID-19 patients. In this regard, Franco et al observed that the implementation of non-invasive respiratory support outside the ICU had favorable results, with an overall mortality rate of 26.9% (22). Similarly, we observed that mortality in IMCU patients who did not require ICU admission was 24.2%, signi cantly lower than in the ICU group.…”
Section: Discussionsupporting
confidence: 76%
“…Recent experience in COVID-19 related Acute respiratory failure (21 publications including 1553 patients) 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 with HFNC, CPAP and Bi-Level Ventilation (using negative pressure rooms in only one series 15 ) shows average success of 60%, 55% and 59%, respectively, and an average infection rate in health professionals of 5.2%, less than the 12% reported in New York City among the staff not necessarily working with NIRT. 28 …”
mentioning
confidence: 99%